Under the new economic model, what is the most effective mecahnism to distribute energy subsidy? a study in Sabah and Sarawak - Caroline Geetha Arokiadasan; Vivin Vincent Chandran; Qaiser Munir; Jainurin Justine @ Abdul Aziz (Universiti Malaysia Sabah, 2013)
NO ABSTRACT